2005
DOI: 10.1179/146532805x58094
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant activity in measles

Abstract: There was a statistically significant difference between the groups for all parameters. All of the anti-oxidant activities except for albumin level were increased in the study group. Both enzymatic and nonenzymatic anti-oxidant defence systems were affected in measles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…In previous studies in literature, Caksen et al 20 showed that although serum alpha-tocopherol, beta carotene, retinol, ascorbic acid, and glutathione levels were significantly higher in SSPE patients, glutathione level was significantly lower and the oxidative stress levels in the patient group were significantly increased compared to the control group. Cemek et al 18 examined the levels of enzymatic antioxidant parameters (superoxide dismutase, glutathione peroxidase, and catalase) and non-enzymatic antioxidant parameters (ceruloplasmin, albumin, total bilirubin, and uric acid) in children with measles and healthy control subjects. They also found that with the exception of albumin, the levels of the antioxidant parameters increased in the patients with measles compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies in literature, Caksen et al 20 showed that although serum alpha-tocopherol, beta carotene, retinol, ascorbic acid, and glutathione levels were significantly higher in SSPE patients, glutathione level was significantly lower and the oxidative stress levels in the patient group were significantly increased compared to the control group. Cemek et al 18 examined the levels of enzymatic antioxidant parameters (superoxide dismutase, glutathione peroxidase, and catalase) and non-enzymatic antioxidant parameters (ceruloplasmin, albumin, total bilirubin, and uric acid) in children with measles and healthy control subjects. They also found that with the exception of albumin, the levels of the antioxidant parameters increased in the patients with measles compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In another 2 studies of patients with measles, oxidative stress levels were seen to be significantly increased in the patient group compared to the control group, which was in line with the findings of the current study. 18 , 19 Erbay et al 32 examined the plasma malondialdehyde (MDA), the serum carbonyl, and the plasma total sulfhydryl levels in 25 patients with measles and 25 healthy control subjects. From the study results it was reported that the plasma MDA and the serum carbonyl levels were higher in the patient group compared to the control group and the plasma sulfhydryl levels were lower in the patient group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these antioxidant activities except for albumin level were increased in children with measles. 14 We also measured malondialdehyde (as a marker of lipid peroxidation and indicator of oxidant activity), reduced glutathione, beta-carotene, retinol, alpha-tocopherol, and ascorbic acid levels in children with measles. Non-enzymatic antioxidant status was found to be decreased, but lipid peroxidation was increased in children with measles.…”
mentioning
confidence: 99%